Cellular and Functional Physiopathology of Bull Sperm With Altered Sperm Freezability - Hitit, Mustafa; Ugur, Muhammet Rasit; Dinh, Thu Tran Nhat; Sajeev, Dishnu; Kaya, Abdullah; Topper, Einko; Tan, Wei; Memili, Erdogan (Frontiers in Veterinary Science, 2020)
The objective of this study was to ascertain the cellular and functional parameters as well as ROS related changes in sperm from bulls with varied sperm freezability phenotypes. Using principal component analysis (PCA), the variables were reduced to two principal components, of which PC1 explained 48% of the variance, and PC2 explained 24% of the variance, and clustered animals into two distinct groups of good freezability (GF) and poor freezability (PF). In ROS associated pathophysiology, there were more dead superoxide anion positive (Dead SO+) sperm in GF bulls than those in PF (15.72 and 12.00%; P = 0.024), and that Dead SO+ and live hydrogen positive cells (live H2O2+) were positively correlated with freezability, respectively (R2 = 0.55, P < 0.0130) and (rs=0.63, P =0.0498). Related to sperm functional integrity, sperm from PF bulls had greater dead intact acrosome (DIAC) than those from GF bulls (26.29 and 16.10%; P = 0.028) whereas sperm from GF bulls tended to have greater live intact acrosome (LIAC) than those from PF bulls (64.47 and 50.05%; P = 0.084). Sperm with dead reacted acrosome (DRAC) in PF bulls were greater compared to those in GF (19.27 and 11.48%; P = 0.007). While DIAC (R2 = 0.56, P = 0.0124) and DRAC (R2 = 0.57, P < 0.0111) were negatively correlated with freezability phenotype, LIAC (R2 = 0.36, P = 0.0628) was positively correlated. Protamine deficiency (PRM) was similar between sperm from GF and PF bulls (7.20 and 0.64%; P = 0.206) and (rs=0.70, P =0.0251) was correlated with freezability. Sperm characteristics associated with cryotolerance are important for advancing both fundamental andrology and assisted reproductive technologies across mammals.